LANGUAGE ADVISOR NIJE – NEGO, REČNIK NEPRAVILNOSTI U KNJIŽEVNOM JEZIKU NAŠEM BY D. KOSTIĆ (1911) AS THE FIRST ORTHOGRAPHIC DICTIONARY OF THE SERBIAN LANGUAGE - Zeljić, Goran (Metodička teorija i praksa, 2025)
The paper analyzes the language guide Nije – Nego by D. Kostić as the first orthographic dictionary of the Serbian language. Without scientific pretensions, this handbook was primarily intended for general practice, as a guide that could assist everyone for whom language is a tool—journalists, writers, editors, proofreaders, teachers. Before Kostić’s guide, Serbs did not have normative works in the dictionary form: Čuturilo’s orthographic handbook from 1884 and Petrović’s from 1914 did not have orthographic dictionaries. This was achieved only in 1923 with Belić’s Orthography of the Serbo-Croatian Language, the first systematic orthographic handbook among Serbs. In this paper, an orthographic dictionary is understood as an alphabetic list of terms related to orthographic rules covered in our orthographic handbooks – capitalization, writing words together or separately, phonetic changes, abbreviations, punctuation, and orthographic signs. The aim of the paper is to present a language handbook from the first half of the twentieth century and to highlight the significance of such a method of addressing language content in Serbian language teaching. A dictionary, as a form of orthographic handbook, is suitable for quickly finding specific terms and resolving grammatical and orthographic dilemmas that users may have. It does not require knowledge of the literary language norm or the language in general, which is why this handbook is not intended solely for language experts but also for general practice. In Kostić’s handbook (and in two later editions, one of which has the phrase "orthographic dictionary" in the title), a pattern is applied where non-standard forms (on the left side, under the heading Nije) are opposed to standard forms (Nego). This is a very practical way to master the literary language norm, especially since dictionaries like this one point out language phenomena that are not covered in grammar books. It is precisely in this observation that we see the space that handbooks of this form can find in the educational process, as they easily provide examples of language mistakes that Serbian speakers might not even realize are mistakes. In didactic and broader linguistic literature, the teaching of the native language is often described as insufficiently functional, especially at the elementary school level, where crucial grammar and orthography knowledge is acquired. A characteristic of such teaching is the so-called "grammatization," formalistic and verbal, isolated from language practice, and serving as a goal in itself. When we look at grammar textbooks and the accompanying didactic-methodical apparatus, we find certain progress compared to previous observations. In addition to some grammatical handbooks in Serbian that include orthographic dictionaries within them, in the approach to presenting teaching content from grammar, orthography, and language culture, these are most often presented in the form of isolated fragments. Also appearing are so-called "language lessons" that provide examples illustrating violations of certain grammatical or orthographic rules, related to the content covered on those textbook pages and part of the didactic-methodical apparatus. On pages dedicated to a specific language content (grammatical, orthographic, etc.), such examples are often set apart in some way (framed, printed in a different color, in a separate paragraph, etc.), with expressions like Pazi! (Be careful!), Obrati pažnju! (Pay attention!), and so on. Since Belić’s Orthography from 1923, orthographic handbooks also feature orthographic dictionaries, which can also be understood as lists of terms that in practice provoke dilemmas and mistakes. This is also pointed out in the teaching process (especially in higher elementary grades and at the high school level). On the other hand, compared to dictionaries like Kostić’s, finding solutions is harder because they rarely point to irregular phenomena, which, once again, are part of everyday language practice, especially among the school population. Handbooks like this one, in the form of an orthographic dictionary, can help authors of grammar textbooks for all ages in selecting appropriate examples for specific teaching units. They have served and will continue to serve lexicographers because normative dictionaries highlight exactly those forms that, from the perspective of the literary language norm, cause dilemmas and mistakes in practice – all with the aim of improving the language culture of everyone who uses the Serbian language.